Integrated application of target-based and ligand-based drug-designing approaches for the identification of novel caspase-6 inhibitors - Chatterjee C.; Ghosh P.; Singh R.; Kumar A.; Singh S.K. (My University, 2025)
Caspase-6 (CASP6) is an effector caspase that has been marked to possess various pathological attributes associated with neurodegeneration. It is widely expressed in the neurodegenerative brain and peripheral tissues. It plays a vital role in apoptotic cell death and also performs non-apoptotic functions like axon pruning which contribute to the degeneration of neurons. Increment in active CASP6 levels in the cerebrospinal fluid has been observed during inflammation and has been linked to the early onset of Alzheimer’s disease (AD). In the current study, a novel CASP6 inhibitor was identified with the help of integrated target-based and ligand-based drug-designing approaches. Various molecular features of US9 (PDB ID 8EG6) were used to generate models. The pharmacophore models were evaluated using the EF value, GH score, and percentage yield to select the best-suited model. The best model was used to screen the ZINC-15 database to obtain virtual hits. The undesirable compounds were eliminated using various nodes in KNIME workflow. The resulting compounds were further subjected to docking-based virtual screening (DBVS) to find the lead compounds. Further, the molecular docking studies were carried out in three stages, followed by pharmacokinetic property prediction and toxicity studies. The top two virtual hits, i.e. ZINC000012563650 and ZINC000069415222, were considered for molecular dynamics simulation studies. Compound ZINC000069415222 was found to possess better stability, drug-like properties, and lower toxicity under simulated conditions. Thus, ZINC000069415222 was identified as a potential CASP6 inhibitor that could be further explored experimentally as an anti-AD drug. © 2024 Informa UK Limited, trading as Taylor & Francis Group.